Two new species of Rhodoveronaea (Rhamphoriales, Ascomycota) from terrestrial habitats in China - Chen, Xue-Mei; Tang, Xia; Du, Tian-Ye; Lu, Yong-Zhong; Suwannarach, Nakarin; Xu, Rui-Fang; Yang, Er-Fu; Elgorban, Abdallah M.; Tibpromma, Saowaluck; Karunarathna, Samantha C. (Phytotaxa, 2024)
During a microfungi investigation carried out in a terrestrial forest in Guizhou Province in China, hyphomycetes on a decaying wood log in a terrestrial habitat were collected. Morphological characteristics and phylogenetic analyses of combined ITS, LSU, SSU, tef1-α, and rpb2 sequence data revealed that the collected hyphomycetes represent two distinct new species in Rhodoveronaea. The two new species introduced in this paper are Rhodoveronaea hyalina and R. lignicola. Full descriptions, illustrations, and a phylogenetic tree to show the placement of the two new species are provided.